Unexistent Art. - Helme, Sirje; Muru, Urmas; Ajaloo Instituudi Galerii, Tallinn; Gallerii Artmaiden, Tallinn; Galerii Harju, Tallinn; Galerii Sammas, Tallinn; Vaal Galerii, Tallinn (Tallinn : Soros Center for Contemporary Arts, 1994)
Adamson, Andres ; Allik, Peeter ; Funk, Karlo ; Graps Grafs, Jan Joonas ; Hmelnitski, Allan ; Kaljo, Kai ; Karmin, Mati ; Kurm, Rainer ; Kurvitz, Raoul ; Kööp, Andro ; Lagle, Ariel ; Laurits, Peeter Maria ; Li, Pier ; Marks, Reda ; Merila, Herkki-Erich ; Ojaver, Jüri ; Pere, Peeter ; Pãrnamets, Tairo ; Reinolt, Rasmus ; Remme, Rauno ; Saks, Jaak ; Sarapuu, Lembit ; Semper, Ene-Liis ; Sheshtakov, Jüri ; Tralla, Mare ; Tõnnov, Margus ; Viljus, Mart ; Vãllik, Martin
biog. p. 11-19
Engels & Ests
Unexistent Art / Olematu Kunst, 2nd Annual Exhibition of the Soros Center for Contemporary Arts, Estonia, 14.10. - 06.11.1994, Ajaloo Instituudi Galerii, Tallinn ; Gallerii "Artmaiden", Tallinn ; Galerii Harju, Tallinn ; Galerii Sammas, Tallinn ; Vaal Galerii, Tallinn
kunstcatalogus
Keywords: Estland